Pengaruh Eksternal Auditor, Komisaris Independen, dan Dewan Pengawas Syariah Terhadap Sustainable Finance Pada Bank Umum Syariah di Indonesia - Weny Rosilawati; Fery Kurniawan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The research evaluates external auditors based on their association with the Big Four Public Accounting Firms, measures independent commissioners by their proportion on the board, and counts Sharia supervisory board members as reported in annual disclosures. Using secondary data from annual and sustainability reports, the study employs multiple linear regression analysis.Results indicate that only independent commissioners have a significant impact on Sustainable Finance, while external auditors and the Sharia supervisory board do not. This highlights the importance of independent commissioners in promoting Sustainable Finance, suggesting that regulators and banks should enhance their roles to strengthen commitments to these initiatives